Waco, Sedgwick County - Jantz, Austin (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study examines the town of Waco, in Salem Township, Sedgwick County, Kansas. It was classified as a town between the dates of 1870 and 1905, but it continues to survive as a community to this day. The town declined due to restricted access to key services, like a bank or railroad, and was unable to compete with the city of Wichita. The included material is based on a variety of sources including photographs, newspapers, and historical accounts.
Austin Jantz, “Waco, Sedgwick County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/199.
Keywords: Sedgwick County; Wichita; Waco; Salem Township; German settlers; German